Cathode voltage and discharge current oscillations in HiPIMS. (4th April 2017) - Klein, P; Hnilica, J; Hubička, Z; Čada, M; Šlapanská, M; Zemánek, M; Vašina, P
Abstract: This paper reports on the oscillations both on the cathode voltage and on the discharge current which emerged suddenly and simultaneously during a high-power impulse magnetron sputtering pulse. Detailed experiments identified the pressure and the discharge current ranges to detect these oscillations. The oscillations originated from the magnetized plasma and their frequency ranged from 225 kHz to 400 kHz depending on the experimental conditions. Simultaneous measurement of both oscillations and spokes was conducted to find mutual correlations. The oscillations always accompanied the spokes and no particular conditions to detect oscillations in the absence of spokes were found. The oscillations were not caused by the rotational motion of the spokes but emerged when a certain threshold amount of spokes was overreached.